Pengaruh Penggunaan Model Pembelajaran Kooperatif Tipe Time Token pada Materi Atmosfer Terhadap Hasil Belajar dan Motivasi Belajar Siswa Kelas X di SMA Negeri 3 Banjar - Agung Wahyudi (Geography Education Study Program, Universitas Samudra, 2020)
The background of this research is the low learning outcomes and learning motivation of class X students at SMA Negeri 3 Banjar on geography subjects. This study aims to determine the effect of the type of time token cooperative learning model on learning outcomes and motivation to learn geography of atmospheric material. The method used in the form of experiments with data collection techniques such as Observation, Questionnaires, Interviews, Documentation, Literature studies, and testsThe results of the cooperative learning model type time token affect the learning outcomes and learning motivation in geographic subjects of atmospheric material based on the results of paired sample t-tests with a value of t calculated 13,510 learning outcomes and 9,334 learning motivation is greater than t table 2.0432, and sig value 0.00 <0.05.